Pengaruh Karakteristik Toko dan Produk Bagi Konsumen di Indonesia Terhadap Pembelian Impulsif - Aditya Halim Perdana Kusuma Putra; Syahnur Said; Sabri Hasan (Jurnal Manajemen dan Kewirausahaan, 2017)
Impulsive buying tendencies can be found in shopping centers such as malls. The number of malls also cause consumer lifestyles  change. Impulsive behavior of puchases is influenced by product characteristics and store characteristics. The purpose of this study is to determine whether the characteristics of stores and products affect the consumer's impulse purchases at malls in Indonesia. This study examines as 435 respondents with descriptive quantitative approach. Questionnaires are disseminated by online system. Data analysis uses a multiple linear regression. Results of this study shows the characteristics of the store and product characteristics significantly affect the impulsive buying.  https://doi.org/10.26905/jmdk.v5i2.1640